Dynamics of communication of women involved in micro-finance projects - Fernandez, Maybel R. (2002)
This paper looks into the communication and cultural implications of the grameen method of banking in Aklan, which involve mostly women. Using interviews and ethnographic techniques, it was found out that women were empowered by their membership in the grameen bank. their income increased and they gained new knowledge on means to earn for their families. They also gained freedom in deciding what small scale business venture to be involved in. The leadership style in the grameen bank depict democratic and undemocratic tendencies. The center chief consulted and involved the women in decision making by communicating problems to them and presenting possible solutions. There were also instances when the center chief's leadership style was oppressive. This forced some members to cease attending meetings or even leave, to the detriment of the rest of the group who had to shoulder the loan default.
Keywords: Microfinance